Explanation behind the less hot Core of the sun than its Corona - Chakrabarti, Kisalaya (International Journal of Computer Sciences and Engineering, 2025)
Core region of the sun is less hot due to absorption of thermonuclear fission (Demass) energy emitted from the Corona. Thermonuclear fusion (Enmass) process is going on the Core region continuously where Hydrogen is converted into Helium. Core region of the sun is gradually expanding. Due to the above cause the Corona region is hotter than Core.